THE ROLE OF STRESS TESTS IN REDUCING BANK LIQUIDITY CRISES: ANALYTICAL STUDY ON A SAMPLE OF COMMERCIAL BANKS - A.M.D. Laith Jawad Kazem; Re.: Woroud Muhammad Hussein (Scholar Express Journals, 2023)
Aims to demonstrate role of (ST) in reducing banking liquidity(BL) crises for private Iraqi banks, to identify indicators of liquidity crises , predictive scenarios for confronting these crises. It investigated role of (ST)scenarios as an independent variable, axis of indicators of banking liquidity crises as a dependent variable, for this purpose, Selecting a sample consisting of three commercial banks, namely (the National Bank of Iraq , Al-Mansour Bank, the Credit Bank), the research was launched So, achieve objectives by following the inductive approach, descriptive approach, analytical approach by studying theoretical framework of (ST)scenarios, (BL) indicators in sample banks. SO, most important ratios to measure, which were represented by four ratios: (liquid assets to total assets, cash credit to total deposits, time deposits to total deposits, cash credit to total assets a set of conclusions, most important of which are: (ST) are considered an early warning tool to determine extent of banks’ ability to overcome crises by predicting crises measuring impact of these tests on banking liquidity indicators. In conclusion, research presented a set of recommendations, Due important of which are: Bank managements should review their investment mechanisms, methods tools focus on harmonizing banking liquidity aspect not neglecting it, as well as exploiting surplus funds in available investment opportunities not freezing them, taking into account special standard ratios and not exceeding them.
Keywords: ST; crises